(untitled) (Comprehensive Journal of Science, 2025)
This study aims to examine the linguistic concepts in Ferdinand de Saussure’s thought through what is mentioned in the book (Course in General Linguistics), which was published in 1916 after his death by his students. The importance of this study lies in clarifying Ferdinand de Saussure’s philosophical linguistic concepts , as they are addressed in the study above through linguistic discourse in linguistic studies, which are rarely studied from a philosophical perspective. In this study, we relied on a descriptive and analytical approach in studying the thought of Ferdinand de Saussure, based on the book Lectures on General Linguistics, in addition to Arabic studies on the thought of Ferdinand de Saussure. The study reached several conclusions: 1- De Saussure distinguished between language, speech, and tongue in his study of linguistic structure. 2- Language is a social convention according to Saussure. 3- Language evolves historically over time. The study recommends more focus and immersion in the study of Ferdinand de Saussure’s linguistic philosophy, especially after the emergence of new manuscripts written in his own handwriting.